P114 Concordance of chlamydia infections of the rectum and urethra in same-sex male partnerships: A cross-sectional analysis. (30th June 2016) - McCall, Hannah; Brima, Nataliya; French, Patrick
Abstract : Background: Sexual health services should ask all high risk attenders about drug and alcohol use. However, the impact of drug and alcohol use on STI epidemiology remains uncertain. Aims: To audit drug and alcohol history taking after introduction of a screening tool and to describe the patterns of use and associations with STI diagnoses. Methods: An anonymised database of all clients attending in 2015 was constructed including basic demographics, reported drug and alcohol history, HIV status and STI diagnoses. Results: 48, 654 clients were seen in 2015. 26, 429 (54%) were asked about drug and/or alcohol use at least once. Use of any drug or excess alcohol was reported by 16% and was associated with higher rates of STIs (24 vs 10%, p < 0.001). Amongst MSM, 62% had a drug and/or alcohol history taken, compared with 47% and 55% in heterosexual men (MSW) and women, respectively (p < 0.0001). STIs diagnoses were significantly higher in drug users compared to non-users (27 vs 11%), but were not different comparing alcohol excess vs no excess (14 vs 13%). STI diagnoses were significantly higher in drug users compared to non-users in all sub-groups – MSM (41 vs 20%) MSW (26 vs 18%) women (12 vs 7%) – all p < 0.0001. Conclusions: The audit showed room for improvement in history taking. Chemsex drugs are associated with the highest risk of STIs. This relationship might not be causal. Party drug use was associated with some STIs. The audit supports drug and alcohol histories for all MSM as well as heterosexual men and women attending with STIs.